Meningkatkan Achievement Productivity Overburden Hauler HD785/CAT777 Dengan Penerapan Fleet Management System-Onboard Fleetsafe Assist - Toni Tanamal; Candra Kartika; Sevira Nur Jannah; Yoga Setya P; Donny Alfitri (CV. Green Publisher Indonesia, 2026)
The actual productivity of overburden loading equipment for the period January to March 2024 of PT Putra Perkasa Abadi jobsite PT Bukit Asam was recorded at only 82% (98.48 Bcm/Hour with a target of 120 Bcm/Hour) with activity cost hauling of 75.4% and loss revenue of IDR 14,676,045,152. This unachievement and loss is the result of the accumulation of several factors that occur at the site, One of the factors is the actual payload of the means of transportation of 94 tons with a target of 105 tons and the actual average speed of 17.2 Km/H with a target of 22 Km/Hour. The non-achievement of payload and speed is due to digitalization that is not optimal, such as speed data, payload, unit position, queue, matching fleet and other data that has not been obtained in real-time by supervisors, so supervision is still limited to manual. Therefore, to support the optimization of digitalization and supervision of the productivity of overburden transportation equipment, PT Putra Perkasa Abadi jobsite PT Bukit Asam uses the Fleet Management System (FMS) – Onboard Fleetsafe Assist (OFA). An increase in the achievement of transportation productivity for the period January 2024 – March 204 by 82% to 100% for the period June 2024 – December 2024, with a reduction cost of IDR 47.2 billion (June 2024 – August 2024) and IDR 65.3 billion (September 2024 – December 2024).